Grounding Pancasila as a Pattern of Behavior through a Joint Educational Movement - Sastroatmodjo, Sudijono (Law Research Review Quarterly, 2016)
Pancasila as an ideology needs to be operationalized in order to become a real pattern of behavior in the life of society, nation and state. Pancasila must become the character of the Indonesian nation as seen in the behavior of daily life. Operationalizing Pancasila as an ideology into the actual behavior of citizens is a joint movement, one of which is through education. The joint movement to ground the Pancasila through education began from the political level of education law in the National Education System Act as a means of shaping the character and character of the nation in accordance with the values of the Pancasila to providing a real example in the practice of life. Teachers in this context are strategic elements in realizing these noble aims and objectives.